How climate change leads to emigration: Conditional and long‐run effects. Issue 4 (8th June 2021) - Helbling, Marc; Meierrieks, Daniel
Abstract: We study the effect of climate change on migration from 121 developing and emerging countries to 20 OECD countries between 1980 and 2010. In contrast to earlier studies, we differentiate between low‐ and high‐skilled migrants to account for the fact that not all groups are equally vulnerable and responsive to climate change. This is also the first study that uses a long‐difference approach. That is, in contrast to earlier studies that investigate short‐term weather changes or weather‐related disasters, we also estimate the effect of climate change on migration over longer time periods. We find that both increasing temperatures and precipitation levels matter to the patterns of migration. We show that increasing temperatures only lead to low‐skilled but not high‐skilled migration (suggesting different migration calculi), are only influential in countries located in hotter parts of the world (consistent with the idea of different levels of vulnerability to climate change), and only materialize in the long run (pointing to the adverse impact of intensification effects due to persistent climate change). Furthermore, we provide evidence that low‐skilled out‐migration is also responsive to short‐ and long‐run precipitation changes.